The study of reproductive outcome and the health of offspring of UK veterans of the Gulf war: methods and description of the study population - Prior Susan; Pelerin Margo; Lewis Samantha; Davies Graham; Doyle Pat; Maconochie Noreen; Sampson Patrick (BMC, 2003)
Abstract Background The aim of this study is to determine whether Gulf war veterans and their partners are at increased risk of adverse reproductive events and whether their children have increased risk of serious health problems. Methods and response to the study are reported here. Methods This was a retrospective cohort study of reproduction among UK Gulf war veterans, with a comparison cohort of Armed Service personnel who were not deployed to the Gulf. Reproductive history and details of children's health was collected by means of a validated postal questionnaire. A separate study of non-responders was conducted. Results Questionnaires were returned by a total of 25,084 Gulf war veterans (24,379 men) and 19,003 (18,439 men) subjects in the comparison group. After adjusting for undelivered mail the response rate was 53% for Gulf war veterans and 42% for non-Gulf veterans among men, 72% and 60% among women. Data from the non-responder study suggests that failure to respond to the main survey was largely unrelated to reproduction. 11,155 (46%) male Gulf war veterans and 7,769 (42%) male non-Gulf war veterans had conceived, or attempted to conceive, since the Gulf war. They reported 16442 and 11517 pregnancies respectively in that period. For women, 313 (44%) Gulf veterans and 235 (42%) non-Gulf veterans reported 484 and 377 pregnancies respectively conceived since the Gulf war. Conclusions This survey enabled collection of information on a range of reproductive outcomes from veterans of the Gulf war and a suitably matched comparison cohort. Although the response rate for men was disappointing, selection bias related to reproduction does not appear to be strong in these data.